Empowering post-stroke older adults through wheelchair development: a conceptual synthesis for stigma reduction and well-being enhancement - Chu, Qingqing; Hasley bin Ramli, Saiful; Ahmad, Siti Anom; Mansor, Noranita; Rokhani, Fakhrul Zaman; Li, Ziming; You, Donggui; Yu, Xinxin (Taylor and Francis, 2024)
Purpose: After a stroke, older adults may encounter social stigma due to their disability and age. This can cause emotions of shame, low self-esteem, and social isolation. The use of assistive devices can make the stigmatizing conditions even more difficult. This study attempts to establish a conceptual framework for designing wheelchairs that can help reduce stigma and improve the well-being of older people with lived experience of stroke.Method: The study utilized the research question construct classification to identify three primary research questions. To address these questions, a bibliographic search was performed using Scopus, Web of Science databases, and PubMed. Articles were selected based on their relevance to the development of wheelchairs and their focus on reducing stigma or enhancing well-being for post-stroke older adults.Results: Seventy articles were chosen to be meticulously reviewed and categorized into sub-themes. This categorization led to the creation of a comprehensive synthesis summary to address each question. The results are further synthesized to formulate a potential theoretical proposition for future investigation. The results suggest enhancing wheelchair design focusing on visibility, symbolism, usefulness, aesthetics, and adaptability through user empowerment and cultural interventions that can effectively reduce stigma, thereby improving the well-being, self-competence, and life quality of post-stroke older adults.Conclusion: The findings offer a design framework for wheelchair innovation specifically aimed at reducing the stigmatizing conditions to improve the well-being of post-stroke older adults through an interdisciplinary perspective. This study suggests further research to explore specific design strategies for wheelchair innovation across various contexts and cultures.